Analisis Strategi Pemasaran Kewirausahaan UMKMKuliner (Studi Kasus pada UMKM ”Butter Sweety” di Bandar Lampung) - Daud, Syahril; Jericho, Jericho; Budianto, Kevin Alexander (Innovative: Journal Of Social Science Research, 2025)
This study analyzes the influence of marketing strategies on MSME Butter Sweety. Using a qualitative approach through in-depth interviews and participant observation, a SWOT analysis was conducted to identify strengths, weaknesses, opportunities, and threats. The results indicate that the strength of MSMEs lies in product quality and good marketing strategies, although there are weaknesses in digital promotion and product diversification. Opportunities lie in the e-commerce market and consumer trends that favor high-quality products, while threats come from intense competition and changes in consumer trends. The proposed strategies include developing premium products, strengthening cultural heritage narratives, and expanding distribution networks through local partnerships. This study provides strategic insights for developing a business model that is more responsive to market needs.